Aflatoxin control projects launched in southern Africa - Dubois, T.; Bandyopadhyay, Ranajit (2012)
Aflatoxins, produced by the fungus Aspergillus flavus, are a major health concern because of their acute and chronic health effects on humans and domesticated animals. The Centers for Disease Control (CDC) estimates that more than 4.5 billion people in the developing world are chronically exposed to aflatoxins through diet. High doses cause serious illness like acute liver cirrhosis and death. Chronic exposure is widespread, leading to nutritional and immunological effects, and cancer. For example, two independent studies have linked aflatoxin to immune suppression, increased susceptibility to diseases (e.g. HIV and malaria), and possible compromised vaccine efficacy. Of particular concern is aflatoxin’s role in reduction of child growth and development. Since chronic diseases in developing countries are underreported, acute aflatoxicosis outbreaks, like the ones recently documented in Kenya with over 100s of deaths, are likely to be an underestimation of the true size of the problem.